African swine fever virus introduction into the EU in 2014: Experience of Latvia. (April 2016) - Oļševskis, Edvīns; Guberti, Vittorio; Seržants, Mārtiņš; Westergaard, Jørgen; Gallardo, Carmina; Rodze, Ieva; Depner, Klaus
Abstract: African swine fever (ASF) virus was introduced in Latvia in June 2014. Thirty-two outbreaks in domestic pigs and 217 cases in wild boar were notified in 2014. Twenty-eight outbreaks (87.5%) were primary outbreaks. The contagiosity within pig herds was low. Failure to use simple biosecurity measures to reduce the chance of virus introduction, for example by inadvertent feeding of locally produced virus contaminated fodder were the main causes for the outbreaks in backyard holdings. The infection in wild boar survived locally in two different areas with a low prevalence and a slow spread. The persistence of the infection in wild boar within an area was most probably linked to wild boar scavenging the carcasses of infected wild boar. Highlights: Epidemiology of African swine fever in domestic pigs and wild boar population in Latvia was analysed. The reason of outbreaks in pig farms was low biosecurity level. African swine fever in domestic pigs and wild boar is characterized by a slow spread (low contagiosity).